A137 COLONOSCOPY RELATED ADVERSE EVENTS IN A POPULATION-BASED COLON SCREENING PROGRAM. (26th February 2020) - Tomaszewski, M; Sanders, D; Enns, R A; Gentile, L; Nash, C; Cowie, S; Petrunia, D; Mullins, P; Azari-Razm, N; Bykov, D; Telford, J J
Abstract: Background: The British Columbia Colon Screening Program (BCCSP) is a population-based program enrolling 50–74 year old individuals for biennial FIT (OC-Sensor, cut-off 10 mcg/g) with follow-up colonoscopy for positive FIT. The neoplasia detection rate is 50–55% and over 75% of colonoscopies have a specimen taken. Previously reported colonoscopy adverse event rates for FIT based screening programs vary widely: 0.03–6.2% and 0–2.7% for bleeding and perforation, respectively. Mortality as a result of colonoscopy is rare but has been reported in 0.0004%-0.0074% of colonoscopies. The rate of colonoscopy related adverse events in BCCSP participants is unknown. Aims: To determine the rate of colonoscopy related serious adverse events within the BCCSP. Methods: This is a retrospective cohort study of all participants undergoing colonoscopy in BCCSP from November 15, 2013 to December 31, 2017. BCCSP contacts screening participants by phone 14 days post colonoscopy to determine unplanned medical visits the day prior (during bowel preparation) or following the colonoscopy. Unplanned events underwent chart review if the event was a perforation, cardiovascular or respiratory event, or resulted in death, hospitalization, or significant intervention including repeat colonoscopy, interventional radiology, surgery, blood transfusion, cardioversion, casting of a fracture or suturing of a laceration. Chart review was conducted by a Colonoscopy Lead and reviewed by BCCSP Quality Committee. Unplanned events were defined as serious adverse events (SAE) if they resulted in death, hospitalization or significant intervention and further classified as probably, possibly, or unlikely related to the colonoscopy. Results: A total of 108, 004 colonoscopies were performed. Unplanned events were reported in 1753 participants, of which 586 met criteria for review. Of these, 578 were confirmed unplanned events and 409 were SAEs of which 367 (89.7%) were probably, 22 (5.4%) possibly and 20 (4.9%) unlikely associated with colonoscopy. 36/10, 000 colonoscopies were associated with a SAE that was probably or possibly related: perforation in 5/10, 000, bleeding 22/10, 000. Three deaths occurred in the 14 days following colonoscopy that were probably (2 perforations) or possibly related to the colonoscopy (0.3/10, 000). Conclusions: The BCCSP has a colonoscopy SAE rate in keeping with previous publications, particularly in the context of a very high proportion of procedures associated with polypectomy, a known risk factor for perforation and bleeding. This study will help inform screening participants about the risks of colonoscopy in the BC program. Future studies are required to confirm these rates using hospital admission data. Funding Agencies: None